2020 Costa Rican Nationally Determined Contribution - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The Nationally Determined Contribution revised for 2020 set the objective of the greenhouse gas emissions reduction of Costa Rica and 13 strategic sectors.